PENDIDIKAN KELUARGA YANG MEMAHAMI PERBEDAAN INDIVIDU; PENENTU MOTIVASI BELAJAR ANAK SECARA DARING DI MASA PANDEMI COVID-19 - Rahmawati Darussyamsu; Neviyarni Suhaili (LP4MK STKIP PGRI Lubuklinggau, 2020)
The Covid-19 pandemic made a change in the learning process from offline to online. This has inevitable positive and negative effects from various aspects, such as learning objectives, students, educators, infrastructure, and the learning environment. All aspects of education that used to take place predominantly in schools are now all at home. Therefore, the key aspect of implementing education is now played by parents. But, the problem is, not all of parents have adequate knowledge about how to educate children and the psychological aspects that accompany it. The individual difference factor is the main aspect that determines children success in learning. This happens with the interaction between the accuracy of parental treatment that takes into account individual differences, thus making children motivated in learning. When the children’s learning motivation is good, the learning will take place effectively and make a meaningful contribution to the childs’ life. Thus, parents must strive for this achievement in order to get good results in children’s education even during the pandemic.